2010
DOI: 10.1002/adsc.200900768
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) Acetate: A Structurally Simple but Highly Efficient Dinuclear Catalyst for Copper‐Catalyzed Azide‐Alkyne Cycloaddition

Abstract: In this article, the structurally well-defined dinuclear complex copper(I) acetate was studied in detail and was developed as a highly practical and efficient catalyst for the copper(I)-catalyzed azide-alkyne cycloaddition. The "bare" phenylethynylcopper(I) (i.e., with no exogeneous ligands) was isolated as an intermediate, which can be converted into an active catalytic species by treatment with acetic acid (in situ produced in the reaction) to efficiently catalyze the azide-alkyne cycloaddition under mild co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 57 publications
(16 reference statements)
2
86
0
1
Order By: Relevance
“…Such a change in colour has also been reported for CuAAC catalyses with copper(I) acetate [74] and is attributed to the formation of transient alkyne or acetylide copper complexes, [35,74,76] which have not been structurally identified. However, in the course of the reaction, 1,2,3-triazoles are formed, which can substitute the alkyne ligands.…”
Section: Variation Of Catalystmentioning
confidence: 69%
See 1 more Smart Citation
“…Such a change in colour has also been reported for CuAAC catalyses with copper(I) acetate [74] and is attributed to the formation of transient alkyne or acetylide copper complexes, [35,74,76] which have not been structurally identified. However, in the course of the reaction, 1,2,3-triazoles are formed, which can substitute the alkyne ligands.…”
Section: Variation Of Catalystmentioning
confidence: 69%
“…[73] Only recently, the potential of copper(I) acetate as heterogeneous catalyst for CuAAC reactions has been investigated by the group of Wang. [74] The authors of this study had noticed that the Cu-Cu distance found in polymeric copper(I) acetate [(CuH 3 CCO 2 ) 2 ] n (2.556 Å) was in the same range as the distance for effective CuAAC catalysis with dinuclear copper(I) complexes as calculated in a DFT study by Ahlquist [32] (transition states with Cu-Cu distances of 2.54 Å for L = chloride and 2.64 Å for L = acetylide).…”
Section: Catalysts For Cuaac Reactionsmentioning
confidence: 99%
“…[4a] CuPPh 3 CN, [21] or CuOAc [22] in solvents that provided the best activity for these catalysts in our hands: D 2 O for CuSO 4 and CuPPh 3 CN, and CD 3 OD for CuOAc (24 h reaction profiles are given in the Figure S3 of the Supporting Information).…”
Section: Tren)]mentioning
confidence: 99%
“…66 Its superiority when compared to other copper(I) salts such as CuCl, CuBr or CuCN was suggested to be due to its dinuclear nature, very similar to the alkynyl copper(I) intermediate 37 proposed by DFT studies (Figure 7). A number of triazoles could be prepared in excellent yields using 1-0.5 mol % 37 (loadings of only 0.01 mol % were also showed efficient for a model reaction) at room temperature under neat conditions.…”
Section: Oxygen Ligandsmentioning
confidence: 99%